CORPORATE SOCIAL RESPONSIBILITY AND TOURISM INDUSTRY: STAKEHOLDER APPROACH - Suleiman JAMAL MOHAMMAD; Lara AL-HADDAD; Muhammad SAFDAR SIAL; Peng WAN (Geo Journal of Tourism and Geosites, 2020)
In terms of tourism companies, the corporate social responsibility commonly known as (CSR) can be addressed as basic guidelines for tourism business which enable them to assimilate environmental, socio-economic, and political concerns of indigenous people and local businesses in line with their own goals and objectives. In the modern era corporate social responsibility is seen in the context of multiple stakeholders. These stakeholders are not only considered as a beneficiary but also considered as partners in any such activity. Nowadays it has become an integral part of tourism companies’ policies and strategies. Its growing importance can be accessed from the fact that over 70% of research articles on the topic have been published in the last half of the decade. The main focus of this study is the evolution of corporate social responsibility in terms of literature and identifying the potential gaps in the present body of literature from the stakeholder's perspective. Present research mainly takes into account the tourism industry and challenges the earlier approaches adopted by the researchers to assess corporate sustainability by incorporating the latest empirical evidence. The evidence point towards the importance of incorporating the stakeholder's perspective in terms of research. This evidence also stresses the importance of incorporating policies about corporate social responsibility at stages of any tourism business at both the planning and execution level.